Colloidal Particles in Tuna Head Soup: Chemical Localization, Structural Change, and Antioxidant Property - Ma, Chenchen; Liu, Pingping; Tao, Ningping; Wang, Xichang; Deng, Shanggui (Frontiers in Nutrition, 2021)
In this work, chemical localization, structural changes, and antioxidant properties of tuna colloidal particles (TCPs) in boiling tuna head soup were examined. The results demonstrated TCPs might be core-shell colloidal spherical structure. The hydrophobic core consisted of triglycerides and chloride ions. The hydrophilic shell layer consisted of chloride ions, sodium ions, phospholipids, protein, and glycosyl molecules. Coalescence of TCPs occurred during the boiling process and water may enter the hydrophobic core of TCPs after the boiling time of 60 min. TCPs had excellent antioxidant properties against H2O2-induced human umbilical vein endothelial cells injury. It might be resulted from that TCPs could decrease cell apoptosis proportion and down-regulate mRNA levels of endoplasmic reticulum bounded chaperone protein glucose related protein (GRP78), C/EBP homologous protein (CHOP), and activating transcription factor-4 (ATF4). This work can provide useful basic information to understand the colloidal system in foods, especially in soup. In addition, it may also promote the potential high-value-added utilization of aquatic by-products.